The Comparison of MinangKabau Dialect in Desa Kampung Baru (Pariaman) and Jorong Pasar Tanjung Gadang (Sijunjung) - Raflis Raflis; Harjoeni Afdhal (Fakultas Sastra Universitas Ekasakti, 2021)
Indonesia is a multi-ethnic country consist of various races religions, ethnic groips, cultures and language, in Minangkabau we can found in every area in Minangkabau, which are called dialects, one of them are the dialect of Desa Kampung Baru (Pariaman) and Jorong Pasar Tanjung Gadang (Sijunjung) Dialect. the differences of language in area region in Minangkabau influenced by cultural factors, geographical factors and socials factor, that make language become varied, therefore the the researcher interested to analysis about it and took the research about dialect, the title of this research is the comparison of Minangkabau Dialect between Desa Kampung Baru (Pariaman) and Jorong Pasar Tanjung Gadang (Sijunjung), aim to describe the differences on phonological (phoneme) and lexical dialects of the language in two regions of Minangkabau, speciallyat Desa Kampung Baru (Pariaman) and Jorong Pasar Tanjung Gadang (Sijunjung), the method used in this research qualitive descriptive, the technique used is the conversational by telephone calls and listening the informant to get the information about the phoneme that they speak, after that the researcher take note and then used of the data cross-checking technique. In this research a significance change in vocabulary was found, that are phoneme / a / changes into / o /, phoneme / r / changes into / w /, phoneme / r / changes into / y /, phoneme / a / changes into au, and phoneme / a / changes into / iu / and The uniqueness vocabulary changes.